Origin and evolution of granites in the world-class Gejiu Sn-Cu-polymetallic ore district: Implications for mineralization and tectonic setting - Guangjie Li; Yongqing Chen; Xu Zhu; Rong Yang (Journal of Geochemical Exploration, 2026)

Effects of equivalence ratio on vented H2/CH4/air explosions in the chamber with a hinged vent panel - Hongzhe Rong; Jialin Li; Jin Guo; Yiming Wang; Zhongrui Chen; Fuqiang Yang (Fuel, 2026)

High-yield hydrogen production via dolomite/ilmenite synergistic catalytic gasification in a fluidized bed reactor - Shaosheng Fang; Panting Li; Dongfang Li; Shaoxiang Pu; Rong Yang; Aoyang Zhang; Xing Zhu; Hairui Yang; Man Zhang; Hua Wang (Fuel, 2026)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Magnetic biochar as dual-functional mediator for low-field magnetic separation of vivianite and membrane fouling mitigation in anaerobic membrane bioreactors - Feng-Ai Yang; Ying Dong; Jifei Chang; Rong Chen; Xin Wang; Juncheng Liu; Fernanda Leite Lobo; Devard I. Stom; Nan Li (Bioresource Technology, 2026)

Exploration of shared gene signatures and molecular mechanisms between psoriasis and COVID-19: evidence from transcriptome data - Rong-Jing Dong; Lu-Hui Yang; Yu-Ye Li; You-Wang Lu (Mammalian Genome, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

Three-dimensional settling map for intelligent detection of activated sludge (AS) properties and health evaluation of AS based wastewater treatment - Jie Lei; Zhe Liu; Guoning Huang; Jiaxuan Wang; Rushuo Yang; Ying Du; Tianyu Han; Zhuangzhuang Yang; Ang Li; Yongjun Liu; Zhenmin Luo; Rong Chen (Water Research, 2026)

Cropping diversification increases microbial network complexity associated with enhanced soil multifunctionality and resistance to global change - Qian Guo; Peng He; Rui Li; Rong Yang; Jianing Wang; Tengfei Ma; Ning Ling; Lina Zheng; Zhaoming Wang (Soil and Tillage Research, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Deep-water carbonate chemistry and CaCO3 burial in the North Indian Ocean since the last glaciation - Jie Tian; Rong Xiang; Sui Wan; Yi Zhong; Fuchang Zhong; Yiping Yang; Wubiao Li; Liyuan Wu; Ping Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Leaching of scandium from a basalt weathering crust-type scandium deposit: An alkali-acid combined treatment method - Xiaorui Wang; Ruidong Yang; Wei Cheng; Rong Chen; Jun Chen; Xinzheng Li (Minerals Engineering, 2026)

Bacterial cellulose guided In-Situ growth of ZIF-8 toward hierarchical N-doped porous carbon for enhanced CO2 capture - Shijie Wang; Xudong Zheng; Sifan Bao; Zihuai Xu; Zhouzhou Yang; Wei Sun; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2026)

High-speed air circulation preserves curcumin bioactivity and enables pH-dependent intestinal release in oyster-based functional foods for IBD dietary intervention - Shuang Gao; Xue Jiang; Yi Rong; Huanhuan Chi; Ci Song; Shujia Wang; Ying Li; Jingjing Chen; Lida Yang; Huawei Ma (Food Research International, 2026)

Co-N4 anchored porphyrin-based COFs enable sacrificial-agent-free photocatalytic extraction of dispersed uranium resources - Chongheng Li; Jinjiao Pan; Yue Ma; Huazhen Rong; Yilei Zhang; Zhuoming Yang; Yifei Zhou; Chuan Gan; Yihui Yuan; Ning Wang (Desalination, 2026)

Unlocking dual-site regulation in perovskite-modified separators for efficient polysulfide conversion in lithium-sulfur batteries - Mingxu Li; Byeong hun Oh; Heejin Kim; Dong-Ho Baek; Ying Liu; Dengzhou Liu; Zabrian Dirfan; SuHyeon Ahn; Rong Yang; Jou-Hyeon Ahn; Inseok Seo; Du-Hyun Lim; et al. (Chemical Engineering Journal, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

In situ formation of chemically integrated and mechanically interlocked interphases enables robust epoxy-copper adhesion - Ting Xin; Zeyu Zheng; Zuo Li; Yue Wu; Yang Liu; Binbin Zhou; Jibao Lu; Xiaoliang Zeng; Fan Yang; Gang Li; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2026)

Orders-of-magnitude reactivity enhancement in persulfate activation by curvature-dependent oxygenated carbon nanotubes - Xin Yang; Zhongyuan Guo; Pufan Wang; Justin Prabowo; Yangyang Wang; Jiaxiang Chen; Jiacheng Wu; Xinyi Huang; Yichen Feng; Chengli Rong; Fangzhou Liu; Hao Li; et al. (Chemical Engineering Journal, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Seasonal dynamics and sedimentary implications of OH-GDGTs in an alpine stratified lake - Jingjing Li; Fanfan Meng; Qian Wang; Rong Wang; Huan Yang; Xiangdong Yang; Jianjun Wang (CATENA, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Spatiotemporal dynamics of PFAS ecological risk in major Chinese river networks: a data-driven assessment (2011–2024) - Letian Zhang; Wei Lin; Zhouyun Xie; Yewei Wang; Rong Wu; Jiaqi Yang; Nanyang Yu; Xiaodong Li; Jie Liang (Water Research, 2026)

DNA methylome analysis reveals EjABCG23-mediated epigenetic regulation underlying fruit russeting in white-fleshed loquat - Kun Zhang; Yuying Ding; Rong Su; Chang Liu; Xuelian Li; Yang Wang; Yan Deng; Qiong Zhou; Xiaojun Chen; Yuxing Li; Qunxian Deng (Postharvest Biology and Technology, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Anomalously low winter sea surface temperatures during the holocene thermal maximum: A novel proxy from the Northern South China Sea - Yiping Yang; Rong Xiang; Fuchang Zhong; Lanlan Zhang; Sui Wan; Wubiao Li (Global and Planetary Change, 2026)

Addressing fruit allergen detection gaps: A validated LC-MS/MS method for eight allergenic fruits in foods - Yingnan Shencheng; Meizhen Zhou; Yumeng Zhao; Siyi Li; Yutong Xu; Yanan Gao; Xiaoxue Jia; Min Gao; Rong Zhang; Shuyan Liu; Feng Ye; Ya Zhang; et al. (Food Chemistry, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Conjugation-enhanced crown ether-based polymer for “locking-controlled” recognition and confined space synergistic co-capture of Sr(II) and U(VI) - Qi-Dong Ye; Jie Wang; Yang Li; Yang Wang; Zi-Hao Feng; Dong-Qing Huang; Yun Wang; Shuang Yang; Rong Hua (Desalination, 2026)

Electromechanically reconfigurable graphene-hydrogel sensor with stress-buffering interface for multi-functional sensing - Yi Wang; Chenling Wu; Yixiao Li; Kun Zheng; Tong Li; Yutao Song; Chan Ye; Zheng Fang; Chenxin Zhu; Ming Zhang; Rong Yang; Lei Liao (Chemical Engineering Journal, 2026)

Autogenous dentin graft material promotes bone regeneration involving OPN/CD44-mediated BMSC recruitment - Xin Deng; Jianmin Zhuo; Yanyan Yang; Ziliang Zhou; Jing Li; Rong Rong; Weihong Chen; Jiashen Chen; Siwen Yu; Siyuan Chen; Lu He; Janak Lal Pathak; et al. (Chemical Engineering Journal, 2026)

The microalgae-bacteria symbiotic inoculation enhances sandy soil multifunctionality and wind erosion resistance through microbial network reorganization - Lianhao Sun; Xin Sun; Haonan Zhang; Hui Nie; Chong Li; Xin Liu; Haidong Li; Xiongfei Zhang; Qianqian Liu; Jingyi Zeng; Weiqi Meng; Guoshuai Hou; et al. (CATENA, 2026)

Enzymatic Preparation of Ejiao (Colla Corii Asini) Peptides and Their Preliminary Mechanism of Melanogenesis Inhibition - Xichao Fu; Shangwei Guo; Meijin Li; Zhijie Chen; Dan Liu; Cuicui Men; Na Yang; Xiaobo Duan; Xiaolu Tang; Yaru Zhang; Haibin Liu; Minghao Liu; et al. (International Journal of Peptide Research and Therapeutics, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Decadal Resampling Reveals Widespread Increases in Soil Microbial Diversity Associated With Nitrogen Deposition - Yi Fan; Yiheng Tao; Bin Hua; Paul Kardol; Yakov Kuzyakov; Shuang Pang; Yi Wu; Tingling Li; Wei Yang; Honghui Wu; Anton A. Goncharov; Anastasia Yu. Korotkevich; et al. (Global Change Biology, 2026)
Simulated manipulation experiments, such as nitrogen addition to mimic atmospheric nitrogen deposition, are widely used in global change research. However, experimental manipulations may differ from real‐world environmental change in their intensity, duration, and co‐occurrence, leaving long‐term changes in soil microbial communities and soil health insufficiently understood. To address this gap, we resampled soils from 38 forest and grassland ecosystems across eastern China in 2009 and 2019 and assessed microbial taxonomic and functional diversity using shotgun metagenomics. Microbial diversity increased by 17% over the decade, accompanied by clear shifts in community composition. Among the environmental variables considered, nitrogen deposition (~19 kg nitrogen ha −1 year −1 across ecosystems) was the strongest predictor of changes in seven of 12 microbial community metrics. Larger nitrogen deposition was also associated with increased relative abundances of nitrogen‐cycling genes and reduced spatial turnover in microbial community composition. These effects were consistent with a potential alleviation of nitrogen limitation and weakening of deterministic community assembly, although these mechanisms could not be directly established. In addition, increases in genes associated with carbon degradation and phosphorus cycling, together with declines in the relative abundances of pathogens, antibiotic resistance genes, and DNA viruses, coincided with the raise of the composite soil health index. Our findings demonstrate widespread decadal increases in soil microbial diversity and soil health across eastern China, with nitrogen deposition emerging as their strongest environmental factor. These results highlight that microbial responses to long‐term ambient environmental change can differ markedly from responses inferred from short‐term or high‐intensity manipulation experiments.

Characterization of CYP402C5 associated with field resistance to three neonicotinoids in Bemisia tabaci - Chao Wang; Rong Zhang; Jing Yang; Mingjiao Huang; Hantang Lu; Ying Zhang; Youjun Zhang; Junkai Li; Xin Yang (Pesticide Biochemistry and Physiology, 2026)

Exogenous dust-induced snow albedo reduction and radiative forcing over the Third Pole - Liang Li; Keqin Duan; Ting Yang; Yuhan Qi; Rong Chen; Peihong Shi (Journal of Hydrology, 2026)

Toxicity-weighted source prioritization of PFAS and antibiotics in an urban watershed - Letian Zhang; Jiaqi Yang; Nanyang Yu; Hao Luo; Zhouyun Xie; Yewei Wang; Rong Wu; Wei Lin; Xiaodong Li; Jie Liang (Journal of Hazardous Materials, 2026)

Divergent responses of ecosystem water use efficiency to environmental drivers in arid versus humid regions - Hailing Li; Maohong Wei; Hongling Yang; Ya Hu; Shaokun Wang; Ping Yue; Xujun Ma; Fangwei Hao; Rong Ma; Xiaoan Zuo (Journal of Environmental Management, 2026)

Potential of RNAi targeting β-N-acetylglucosaminidase(NAG1)for controlling Dendroctonus valens LeConte (Coleoptera: Scolytidae) - Yue Sun; Qin Cao; Yong-Hao Nan; Yang-Nan Hou; Chun-Fang Qi; Ji-Gang Li; Jian-Rong Wei (Journal of Asia-Pacific Entomology, 2026)

Dynamic failure mechanism and wave propagation characteristics of rock with double-layer filled joints - Yanzhe Li; Chuanxin Rong; Runze Zhang; Yang Wang (Geomechanics for Energy and the Environment, 2026)

Co-removal of norfloxacin and Cr(VI) by Co/N-doped carbon activating peroxymonosulfate: 1O2 oxidation coupled with interfacial electron transfer - Yaru Li; Heming Wang; Rong Qiao; Dongxu Zhou; Fuyun Deng; Gaoyang Chen; Peixin Mao; Chaolin Yang; Xiaodong Zhang (Environmental Research, 2026)

Jahn-Teller distortion lowers the kinetic barrier for Co3+/Co4+ redox: A pathway to ultrafast HMF electrooxidation - Dan Liu; Yudong Li; Jian Li; Chengyu Wang; Jingwei Li; Rong Wang; Xiaohui Yang (Chemical Engineering Journal, 2026)

An inflammation-targeted hydrogel for the synergistic treatment of colorectal cancer and associated neuropsychiatric dysfunction - Keying Chen; Na Li; Anni Ren; Lingling Yang; Pei Xie; Yong Gao; Yanwu Li; Ying Tang; Rong Zhang; Huafeng Pan; Bangjiang Fang; Tongkai Chen; et al. (Chemical Engineering Journal, 2026)

Electrostatic-field-driven synergistic regulation of molecular conformation and mesostructure enables stable Na+ transport in 12 μm PVDF-HFP-based electrolytes - Jiaze Li; Rong Yang; Xiaobin Li; Aoyi Jiang; Xin Dong; Hongyu Shang; Yinglin Yan; Hyun Woo Kim; Jou-Hyeon Ahn (Chemical Engineering Journal, 2026)

Reconstruction of vegetation and climate variability on the southeastern Tibetan plateau margin over the last 2000 years - Bing Song; Deke Xu; Limi Mao; Rong Wang; Qian Wang; Mingying Quan; Jingjing Li; Zhenyu Ni; Yanjie Zhao; Hao Li; Houyuan Lu; Xiangdong Yang (CATENA, 2026)

Investigation of the regulatory effects of the initial oxidation–reduction potential on lactic acid-producing bacteria in culture and silage fermentation and its metabolic mechanism - Mengxin Li; Yuanjiang Rong; Qiang Yu; Ya Su; Yulong Xi; Yixi Long; Yixiao Xie; Hong Sun; Jun Hao; Fuyu Yang; Yulong Zheng (Bioresource Technology, 2026)

A comprehensive LMUPO research framework: Integrating outdoor urban microclimates into building performance analysis and optimization - Zhixing Li; Yi Yang; Rong Xia; Yanjun Su; Zhuoyang Sun (Building and Environment, 2026)

Indigenous beneficial microbes contribute to pathogen inhibition in Chinese yam continuously cropped soil - Huanhuan Cheng; Yifan Cao; Paidamoyo Mataranyika; Ziyi Yuan; Yan Wang; Jian Yang; Luqi Huang; Zongzhuan Shen; Qirong Shen; Rong Li (Applied Soil Ecology, 2026)

Optimizing inlet design for improved water renewal and solids removal in circular tanks in recirculating aquaculture systems - Huacheng Li; Qiushi Yang; Wenhan Li; Chengchen Jiang; Tingting Xu; Yutian Yuan; Rong Tang; Li Li; Yale Deng; Dapeng Li (Aquacultural Engineering, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Assessing cognitive impairment in epilepsy using Arterial spin-labeled (ASL) perfusion imaging - Qiuyan Chen; Jie Zhang; Rong Chen; Yameng Qin; Xu Wang; Qiang Liu; Zheng Yin; Ping Yang; Feng Rao; Longnan Wang; Mengyun Li; Yanzi Jin; et al. (Brain Imaging and Behavior, 2026)

Assessing impacts of vertical mixing parameterizations on ENSO simulation in a ROMS-based hybrid coupled model - Yinnan Li; Yang Yu; Maonan Chen; Chuan Gao; Hongna Wang; Liu Yang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Rapid Determination of Tight Rock Permeability Using Early-Time Transient Pulse-Decay Data - Minghao Yi; Chaoqi Yang; Liang Wang; Rong Zhang; Kaizhong Zhang; Shuqing Li (Rock Mechanics and Rock Engineering, 2026)

A decomposition-based reinforcement learning approach for production and distribution integrated scheduling problem of perishable products - Yuan-yuan Yang; Bin Qian; Li-jun Wang; Jun-qing Li; Rong Hu (Swarm and Evolutionary Computation, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Impact of fulvic acid on copper exposure in Ulva prolifera: Integrative insights from growth, physiology, transcriptomics, and physico-chemical characteristics - Tongpeng Jia; Geqi Zhang; Yahe Li; Xinchuan Yang; Nianjun Xu; Rong Xiang (Journal of Hazardous Materials, 2026)

Biodegradable plastic mulches: Distinct effects on microbial communities but no impact on soil multifunctionality during cabbage production - Rong Liang; Lei Mei; Jina Ding; Li Wang; Mouliang Xiao; Yongfu Li; Xiao Liu; Changlong Shao; David R. Chadwick; Davey Jones; Fan Ding; Can Hu; et al. (Journal of Hazardous Materials, 2026)

Species-specific bioaccumulation and biotransformation of antibiotics shape differential toxicological effects in a multi-level aquatic community - Bin Wang; Hailing Zhou; Mengting Li; Bingyu Shen; Lidan Zhang; Jiayi Yang; Yushi Fang; You Zi; Jinmei Chen; Yujie He; Rong Ji (Journal of Hazardous Materials, 2026)

Three-stage temperature-ramping stirred-tank bioleaching enhances copper recovery from chalcopyrite by mitigating surface passivation - Rong Nie; Bingyang Tian; Xinlong Yang; He Shang; Wenjuan Li; Jiankang Wen; Hongying Yang (Journal of Cleaner Production, 2026)

Acquisitive, diverse tree stands resist vine invasion via contrasting temporal effects on crown volume and herb cover - Li Zhang; Liting Zheng; Marc W. Cadotte; Charles A. Nock; Baiyu Yang; Zhiming Hu; Ciliang Zhao; Wen-Hui You; En-Rong Yan (Forest Ecology and Management, 2026)

The peroxisome RING-type E3 ubiquitin ligase-mediated peroxisome function is essential for Alternaria alternata pathogenicity: coordinated regulation of lipid metabolism homeostasis and redox balance - Qianqian Jiang; Yongcai Li; Yuanpin Nan; Rong Li; Yangyang Yang; Wenjuan Liu; Yang Bi (Fungal Biology, 2026)

Chymotrypsin-based LC-MS for accurate quantification of 11 major food allergens in heat-processed foods overcoming Maillard reaction challenges - Siyi Li; Meizhen Zhou; Ruijie Chen; Yutong Xu; Yumeng Zhao; Yingnan Shencheng; Shuyan Liu; Rong Zhang; Min Gao; Yi Li; Shupeng Yang (Food Chemistry, 2026)

Role of the immune microenvironment in bone regeneration and progress in immune-modulating bone nanobiomaterials - Rong’an Li; Jiakang Yang; Wenjun Duan; Kexin Yang; Katong Lo; Qianming Chen; Baixiang Wang (Journal of Zhejiang University-SCIENCE B, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Effects of GIAHS conservation on agricultural landscape and ecological sustainability in heritage sites: evidence from the Yuanyang Hani Rice Terraces - Jin-Rong Zhang; Hong-Bo Li; He-Ping Yang; Meng-Na Qi (Environment, Development and Sustainability, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Inhibitory effect of gut microbiota-fermented trisaccharide GuFGa (Glc-Fuc-Gal) on Campylobacter jejuni: insights from transcriptomic and metabolomic analyses - Xinmiao Ren; Shuang Li; Changyun Wang; Francesco Secundo; Ningyang Li; Mengshi Xiao; Min Yang; Rong Li; Qing Kong; Han Sun; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Whole-transcriptome profiling reveals the landscape of host circular RNAs during grass carp reovirus infection - Tian Bu; Dongmei Zhong; Fang Gou; Yinggang Li; Siwan Xu; Yifei Wang; Jinwang Ding; Rong Yang; Shaojun Liu (Aquaculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Non-stationary dynamic responses during continuous load transfer process of float-over installation: Experimental and numerical investigations - Yuhao Wei; Shuqing Wang; Xiancang Song; Gen Rong; Xiang Li; Yiyuan Yang (Ocean Engineering, 2026)

A data–mechanism fusion method for ships collision avoidance based on Probabilistic Velocity Obstacles - Zhuojun Yuan; Junmin Mou; Mengxia Li; Linyin Chen; Pengfei Chen; Hao Rong; Zaili Yang (Ocean Engineering, 2026)

Latitudinal gradients shape adaptive divergence of tea saponin accumulation in Camellia oleifera - Danmei Yu; Liyun Feng; Suyun Zhang; Xiaohua Liu; Huan Yang; Jie Xiao; Shang Chen; Xia Dong; Li Cheng; Yao Zhao; Jun Rong; Jian Zhang (Food Bioscience, 2026)

Mussel-inspired surface modification for high-rate and effectively complex wastewater systems purification - Minrui Zhan; Xi Zhang; Rong Liu; Manman Zhao; Wenkai Li; Huiyu Yang; Jiehao Du; Wei Chen; Shaojin Gu; Xin Liu; Bin Shang (Desalination, 2026)

Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

6H2L, a novel derivative of bifendate, dually suppresses glycolysis and glutaminolysis in hepatocellular carcinoma via inhibiting YAP stability - Beibei Zhang; Kaixuan Sheng; Yue Yan; Xinlei Wang; Xinning Cheng; Rong Liao; Zhiyi Yang; Mengyi Li; Fan Wang; Qi Qi; Yu Wang; Chenglin Li (Chemico-Biological Interactions, 2026)

Seed dispersal drives competition between pair-growing trees: implications for forest community dynamics - Xifu Yang; Haifeng Gu; Guangshun Jiang; Ke Rong; Hongjun Li; Qinghua Zhao; Yanhui Guan; Feifei Yang; Wentao Zhang; Tongzuo Zhang; Zhibin Zhang (Plant Ecology, 2026)

Discovery of pyrrolo[2,3-d]pyrimidine derivatives with inhibitory effect on liver cancer stem cell - Xuecong Zhang; Xuechun Chen; Liwei Wang; Yiyuan Chang; Jiaxin Li; Jijian Yang; Dongxuan Ni; Ruihan Zhang; Rong Liu; Weilie Xiao (Medicinal Chemistry Research, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Species Selection for Oyster Reefs: Growth Simulations of Three Oysters Across Multiple Habitats - Jingyi Liu; Zhenhao Yang; Haoyuan Li; Chenxing Yang; Rong Wan (Fishes, 2026)
Oysters, as sessile organisms, are highly influenced by environmental conditions affecting their growth and reproduction. Therefore, unfavorable conditions can directly compromise the effectiveness of oyster reef restoration efforts. The study applied the dynamic energy budget (DEB) theory to model the growth of the Suminoe oyster (Crassostrea ariakensis) and estimated the model’s main parameters through linear and nonlinear regression methods. Meanwhile, the parameters of the existing DEB models for the Pacific oyster (Crassostrea gigas) and the Portuguese oyster (Crassostrea angulata) were optimized to improve the model performance. Model accuracy was confirmed by comparing the simulated and observed values of shell height and wet weight for three oyster species. The validated models were subsequently applied to three distinct habitats: Qianhu Bay, the Yangtze River Estuary, and Jiaozhou Bay, to simulate the individual dynamic growth and survival processes of the three oyster species. The simulations of shell height and wet weight for the three oyster species showed strong agreement with observations, with a mean coefficient of determination (R2) of 0.98. The mean NRMSE value of the three models was 0.16, indicating low model-prediction error. The simulation of various habitat scenarios suggested that C. ariakensis exhibited faster growth in the Yangtze River Estuary and Qianhu Bay, and C. gigas in the Yangtze River Estuary. Additionally, C. angulata experienced mortality in the Yangtze River Estuary (February) and Jiaozhou Bay (January). The findings of this study can provide scientific guidance on selecting species for oyster reefs across various marine environments to effectively enhance their ecological restoration outcomes.

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Spatiotemporal Patterns, Driving Mechanisms and Responses of Soil Drought to Meteorological Drought in the Yellow River Basin of China - Fei Wang; Wenhan Yu; Yi Zhang; Hexin Lai; Mengting Du; Qian Xu; Rong Li; Ruyi Men; Haoyu Li; Kai Feng; Shikai Gao; Yanbin Li; et al. (International Journal of Climatology, 2026)
With the escalation of global warming, the potential for land evaporation in the Yellow River Basin (YRB) has increased remarkably, and the problem of soil drought has become increasingly prominent. This not only restricts the development of the agricultural economy in the basin, but also intensifies the disparity between water availability and demand, and exerts a profound influence on the ecological security of the basin. In light of this, this study focuses on soil moisture in the YRB from 2000 to 2022, and conducts an in‐depth analysis of the temporal evolution, spatial patterns, abrupt change characteristics as well as the driving forces of soil drought by calculating the Standardised Soil Moisture Index (SSMI). The results show that: (1) Soil drought in the YRB from 2000 to 2022 exhibited a decreasing trend. A negative abrupt change point occurred in February 2004, indicating a sudden intensification of arid conditions. The soil drought in the Above Longyangxia (AL) region exhibited the most significant decreasing trend in September. (2) The most severe soil drought occurred in 2006, and the drought was most intense in November of that year, when the drought‐affected area reaching 86.96%. The severely drought‐stricken areas were predominantly concentrated in the central and northern regions of the basin. (3) The SSMI in the second‐level sub‐regions of the YRB exhibits three types of abrupt changes: increase to decrease, intermittent increase, and decrease to increase, and shows a clear trend from upstream to downstream. (4) The results of cross‐wavelet analysis indicate that soil moisture‐absolute humidity‐soil temperature is the best explanatory combination for soil drought. (5) The slopes of the small‐ and medium‐scale fittings in the AL region are 0.5021 and 0.2584, respectively, and the corresponding mean values of meteorological drought severity are 0.87 and 2.57, respectively. Drought events in the YRB are mainly of medium/short duration and low severity, and soil drought severity tends to increase with the intensification of meteorological drought. This study reveals the spatiotemporal variation patterns of soil drought in the YRB, as well as the responses of climate to soil drought. These findings provide a scientific basis for drought resistance and ecological protection within the basin.

Research progress on the fermentation characterization of non- Saccharomyces yeasts in fruit wines: a review - Rong Zhang; Xiaoyan Hou; Qigao Fan; Kaidi Hu; Lunqiong Hou; Ning Kang; Ziyuan Ou; Ning Zhao; Qin Li; Aiping Liu; Yong Yang; Guoquan Han; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Isolation, identification, and disease-protective potential of Pseudomonas monsensis DBFF02 against Saprolegnia infection in grass carp - Guofan Zhang; Kunyan Li; Yuyuan Peng; Simei He; Chen Li; Rong Fan; Jiajie Xie; Linger Qian; Xinran Long; Jiayi Wang; Jiatao Yang; Yanmin He; et al. (Aquaculture, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Proanthocyanidin/laccase-mediated cross-linking enhances the structural stability and rheological properties of collagen solutions - Junhong Xie; Li Feng; Fanghui Deng; Wei Yue; Wei Liang; Qiannan Zhao; Wentao Ma; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2026)

Depth-coupling pattern between forest soil microorganisms and carbon mineralization in southwestern China - Shuang Ding; Shengzhao Wei; Honghong Lin; Li Rong; Enwei Zhang; Xue Yang; Huanxu Lv; Xingwu Duan (CATENA, 2026)

Unveiling animal death cognition: the role of social systems - Junjie Mu; Xi Yang; Yongbo Li; Yu Huan; Boyi Zhang; James R. Anderson; Rong Hou; Baoguo Li (Science China Life Sciences, 2026)

Improving spatial resolutions of unmanned aerial vehicle hyperspectral images to predict grain yield and protein content in rice - Zhonglin Wang; Rong Hu; Mingming Hu; Huilai Yin; Tao Liu; Yufei Xie; Yangming Ma; Feng Yang; Feijie Li; Zhiyuan Yang; Yongjian Sun; Jun Ma (Precision Agriculture, 2026)

Genome-wide Identification and Expression Analysis of the ABF Gene Family in Achnatherum splendens - Shan Yin; Mingsu Chen; Ming Hu; XiaoYing Li; Jingru Wang; Jiahuan Niu; Zhangqi Song; Huan Yang; Hongbing Li; Rong Li (Plant Molecular Biology Reporter, 2026)

Imbalanced Si:N Alters Lipid Production and Photosynthesis in the Marine Diatom Phaeodactylum tricornutum and Dinoflagellate Prorocentrum donghaiense - Jiaxuan Cui; Chuanli Zhang; Rong Bi; Yunyun Zhuang; Xiaoqian Pan; Xiao Qin; Zhong Cao; Hailong Zhang; Li Li; Yang Ding; Meixun Zhao (Journal of Ocean University of China, 2026)

Novel prenylated diketopiperazines with anti-osteoclastogenic activity from the deep-sea-derived Penicillium limosum ZEN48 - Yong Zhang; Yan-Qing Guo; You Li; Zheng-Biao Zou; Zhe-Wen Chen; Rong Zhao; Robert J. Capon; Tai-Zong Wu; Chun-Lan Xie; Xian-Wen Yang (Marine Life Science & Technology, 2026)
A systematic chemical investigation of the deep-sea-derived fungus Penicillium limosum ZEN48 resulted in the isolation of four new indole-diketopiperazine alkaloids, limopiperazines A–D ( 1 – 4 ), alongside 16 known analogues ( 5 – 20 ). The structures of the new compounds were determined through comprehensive spectroscopic analysis, quantum chemical calculations, X-ray crystallography, and biogenetic considerations. Limopiperazine C ( 3 ) potently inhibited osteoclast differentiation and disrupted actin ring formation. Integrated RNA sequencing, RT-qPCR and molecular docking revealed that limopiperazine C exerts the anti-osteoclastogenic effect by modulating the ferroptosis signaling pathway via targeting heme oxygenase-1 (Hmox-1), positioning it as a promising lead compound for developing anti-osteoporotic agents.

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

Chemical constituents and ferroptosis inhibitory activity of the deep-sea-derived fungus Penicillium citrinum W24 - Cheng-You Lin; Yuan Wang; Tai-Zong Wu; Rong Chao; Zheng-Biao Zou; Li-Sheng Li; Tian-Hua Zhong; Xian-Wen Yang (Natural Product Research, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

HGS+ enlarged vesicular compartments serve as the sites for coronavirus assembly at later infection stage - Xubing Long; Buyun Tian; Rongrong Chen; Rong Bai; Jinping Yang; Yushuang Fang; Xinyue Fu; Yanhong Xue; Wei Ji; Tao Xu; Zonghong Li (Science Bulletin, 2026)

Catechol 1, 2-dioxygenase AaCHD is essential for the detoxification of phenolic acids in pear fruit peel by Alternaria alternata - Rong Li; Wenyi Xu; Yang Bi; Yongcai Li (Postharvest Biology and Technology, 2026)

Brain gray matter atrophy in adult population with cognitive impairment due to chronic cadmium exposure - Zhentao Gao; Longtao Yang; Rong Ma; Xiaoying Li; Fang Pei; Wei Hu; Yixuan Wu; Xiaojiang Tang; Jun Liu (NeuroToxicology, 2026)

High-resolution point source pollution database boosts SWAT-QUAL2K coupled model for multi-scale nitrogen and phosphorus management - Yang Bi; Yanxin Zhao; Yi Rong; Ningtong Li; Kai Huang; Yan Chen (Journal of Cleaner Production, 2026)

Valorization of catalytically improved combustion stability for low-concentration methane in a gradient pore-density porous media burner - Yunqi Cao; Haonan Rong; Li Yang; Yifan Ding; Fang Liu; Cheng Zhai (Fuel, 2026)

Numerical simulation of fracture propagation and interwell frac-hit mechanism in deep shale gas infill wells - Yufeng Wang; Qiang Wang; Jinzhou Zhao; Yongquan Hu; Jianglong Wang; Juhui Zhu; Rong Wang; Xiaowei Li; Yu Yang (Engineering Geology, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Fe-regulated AnMBR for carbon & phosphorus co-recovery and membrane fouling control - Ying Dong; Rong Chen; Jifei Chang; Fengai Yang; Zhen Lei; Xin Wang; Nan Li (Chemical Engineering Journal, 2026)

Nanoscale insights into the immobilization of coexisting As(V) and Cd(II) during Fe(II)-driven ferrihydrite transformation - Wei Li; Zhuohao Wu; Yang Lu; Rong Li; Qianying Sun; Zheng Liang; Wencheng Wu; Zhenqing Shi (Chemical Geology, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Evaluation of protein and metabolic engineering strategies on (−)-α-bisabolol production by Escherichia coli - Jiayi Ma; Rong Fang; Xiaoyuan Yue; Hui Jiang; Qixuan Kong; Tiankuo Jiang; Jiale Yu; Chang Zhou; Yuanyuan Xia; Wei Shen; Haili Liu; Yaqin Shen; et al. (Systems Microbiology and Biomanufacturing, 2026)

Genetic basis of pedicellate spikelet masculinization in maize revealed by an advanced maize–teosinte population - Ruifan Bao; Xueying Wang; Junle Wu; Ting Liang; Xiya Hu; Pengxu Meng; Hang Mi; Peng Li; Sijia Yang; Zhiqin Liu; Siyu Lei; Jinyu Yang; et al. (Planta, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

Nitrogen enrichment boosts subsoil carbon sequestration by enhancing microbial straw utilization - Zheng-Rong Kan; Muhan Li; Xinyue Wang; Yixuan Luo; Ahmad Latif Virk; Gong Wu; Haishui Yang; Feng-Min Li (Plant and Soil, 2026)

Mechanisms by Which Humic Acid Reduces Copper Toxicity in Citrus Roots Based on Omics and Physiology - Wei-Tao Huang; Rong-Rong Xie; Liang-Yuan Tong; Tian-Tian Xia; Jiuxin Guo; Ning-Wei Lai; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Plant Growth Regulation, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Resolving the Trade‐Offs by Conservation Deep Tillage - Zheng‐Rong Kan; Johannes Lehmann; Feng‐Min Li; Rattan Lal; Haishui Yang (Global Change Biology, 2026)

Human MAITregs possess diverse TCR repertoires and are functionally supported by glycolysis - Maoyu Tang; Xinying Li; Xudong Yang; Changfeng Zhao; Yuwei Zhang; Sanwei Chen; Zhenghui Ye; Liujin Hou; Yusheng Chen; Rong Lv; Hongchuan Zhao; Xiaowen Cheng; et al. (Science China Life Sciences, 2026)

The causal relationship between polycystic ovary syndrome and structural changes in brain: a Mendelian randomization study - Han Yang; Wei Xie; Camilo Alberto Pinzon Galvis; Si Huang; Xu He; Si-yi Yu; Qing You; Fan-rong Liang; Zhi-yong Xiao; Ning Li (Brain Imaging and Behavior, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Seco-iridoid and lignans from Gymnosporia acuminata - Yang Liu; Wenhui Suo; Qinggui Li; Qingqing Luo; Rong Wang; Xiaoke Zhang; Changwei Song; Lingjie Meng (Natural Product Research, 2026)

Behavioral, Metabolic, and Monoaminergic Responses to Cooked Diets in Southern Catfish (Silurus meridionalis) - Qiushi Yang; Zhimin Zhang; Tingting Xu; Wenhan Li; Huacheng Li; Rong Tang; Yale Deng; Liqin Yu; Xi Zhang; Li Li; Dapeng Li (Fishes, 2026)
Diet form is increasingly recognized as a welfare-relevant factor in intensive aquaculture, yet the effects of feed cooking on fish behavioral and physiological welfare remain poorly characterized. Juvenile southern catfish (Silurus meridionalis; 6.18 ± 0.52 g) were reared for 6 weeks in an indoor recirculating aquaculture system and fed either raw grass carp (Ctenopharyngodon idella) muscle (fish fed raw muscle, FR) or cooked grass carp muscle (fish fed cooked muscle, FC; 15 min ramp to ~100 °C followed by 2–3 min at ~100 °C). Locomotor activity and anxiety-like behavior were assessed using the open-field test and an annular light–dark preference assay, respectively. Flow-through respirometry further revealed a significantly lower standard metabolic rate (SMR) in FC fish than in FR fish, decreasing from 10.30 to 6.83, which represents a 33.7% reduction. Endocrine and biochemical analyses showed that cooking significantly decreased serum total triiodothyronine (T3) by 23.8%, whereas routine serum biochemical indices remained unchanged. In brain tissue, dopamine (DA) was significantly reduced by 7.2% in the FC group, and RT-qPCR analysis of dopamine-related genes further showed a significant downregulation of the rate-limiting synthesis gene th. These results indicate that cooking primarily downshifts the activity-energy axis in southern catfish and is accompanied by coordinated thyroid and dopaminergic changes. To our knowledge, this is the first integrated study to evaluate the behavioral, metabolic, and neuroendocrine effects of cooked feed in S. meridionalis, providing a short-term phenotypic baseline for assessing welfare-relevant feeding scenarios in aquaculture.

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Antifungal mechanisms of Bacillus velezensis Shannan.BV80-12 extracellular metabolites against the citrus postharvest pathogen Penicillium italicum - Rong Wang; Yali Tan; Feiyan Dong; Jiao Yang; Xiao Li; Tong Gu; Jialan Zhang; Li Li; Mengxiang Gao (Postharvest Biology and Technology, 2026)

Impact of organic carbon composition on bacterial community assembly in organic and mineral soil layers under phosphorus addition in a Robinia pseudoacacia plantation - Ahejiang SAILIKE; Yujie LIANG; Rong FU; Hongjian HAO; Rong WANG; Ning PENG; Shicai LI; Zhouchang YU; Fangxin ZHENG; Wei ZHANG; Yangyang LIU; Peizhi YANG; et al. (Pedosphere, 2026)

Mitigating 2-MIB and odor-producing cyanobacteria in a shallow drinking-water reservoir using sponge‑iron-assisted water-lifting aeration - Fei Zhang; Rong Li; Hao mu; Yuhai Zhuo; Zhi Yang; Tinglin Huang; Nan Li (Journal of Water Process Engineering, 2026)

High hydrostatic pressure mitigates light-induced degradation of volatiles and phenolic compounds in seabuckthorn pear blends - Jianfeng Wang; Yonghao Chen; Rong Zhang; Shengbin Ma; Faisal Eudes Sam; Jixin Li; Yang Bi; Yumei Jiang (Food Chemistry, 2026)

Tropomyosin-targeted LC-MS/MS for quantitative detection of molluscan allergens in foods: Method validation and application - Yumeng Zhao; Peijie Yang; Yingnan Shencheng; Siyi Li; Meizhen Zhou; Min Gao; Feng Ye; Rong Zhang; Ya Zhang; Yi Li; Shupeng Yang (Food Chemistry, 2026)

Precise pH control and synergistic interaction of raw materials improve the quality of stewed beef: multi-omics analysis of tenderization mechanisms and flavor restructuring - Yan Shen; Zezhu Du; Jinya Dong; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Cheng Gong; Shikuan Zhao; Zhiyu Li; Lihui Yu; Rong Geng; Xiaocui Du; et al. (Food Chemistry, 2026)

Ultrasound-assisted dry-heating glycosylation with xylooligosaccharides: Enhancing the structural and functional properties of pig skin collagen - Shengqi Jiang; Lin Li; Hongqing Nie; Jincheng Han; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Huiyu Han; Jing Xi; Wu Ding (Food Hydrocolloids, 2026)

Probabilistic risk assessment of heavy metal(loid)s in traditional Chinese medicinal materials and their decoctions: Integrating dissolution characteristic with Monte Carlo simulation - Guanjun Nan; Zhengzheng Liu; Xuemei Zhou; Yunzhe Li; Fanli Yang; Rong Lin; Guangde Yang (Food and Chemical Toxicology, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Local electric field regulation induces specific catalysis to achieve efficient and selective sensing of methanol - Cundong Feng; Shizhu Ling; Rong Tan; Weian Du; Xueqin Ouyang; Jianjun Xiong; Yangfeng Li; Haoyang Ren; Yingpu Wang; Weifang Liao; Qian Xiao; Wentao Dong; et al. (Chemical Engineering Journal, 2026)

Chemical constituents from Sargentodoxa cuneata and their chemotaxonomic significance - Lu-Shan Li; Huanlai Huang; Jia Yang; Rong-Yuan Deng; Ji-Ye Liang; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2026)

Endometrial microbiota-dimethylglycine-Treg cell axis affects endometrial receptivity in recurrent implantation failure - Fen-Ting Liu; Ping Zhou; Feng Deng; Bao-Ying Liao; Zi Yang; Di Sun; Heng Pan; Yang Yu; Shuo Yang; Rong Li (Science China Life Sciences, 2026)

Efficacy and Safety of Temozolomide for the Treatment of Advanced or Recurrent Ependymoma: A Meta-Analysis - Rong Zhang; Binyan Liu; Zhuang Kang; Shenglan Li; Yingfan Sun; Jiachen Wang; Xin Yang; Shuo Yin; Feng Chen; Wenbin Li (Journal of Pharmaceutical Innovation, 2026)

A CBAM-integrated deep convolutional neural network for weather radar echo correction to overcome terrain occlusion challenge - Hao Wang; Zhihao Liu; Fugui Zhang; Zhi Li; Qiangyu Zeng; Tiantian Yu; Rong Yang (Advances in Space Research, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Salmonella virulence factor sptP activates the NLRP3/Caspase-1 pathway to induce pyroptosis and exacerbate intestinal injury in chicks - Bo Zhang; Ke Li; Hongya Yan; Rong Zhao; Zhenju Yuan; Changrui Xiao; Chengji Yang; Aiguo Xin (Veterinary Microbiology, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Upcycling anaerobic digestion methane to single-cell protein as a low-carbon strategy - Pan-Long Lv; Qing-Rui Hu; Yu-Yang Hu; Wenjing Gong; Qian Li; Rong Chen (Resources, Conservation and Recycling, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Spatiotemporal variations of chlorinated polycyclic aromatic hydrocarbons in Yellow Sea sediments: An eight-year field monitoring study - Xin Yang; Yunyong She; Qian Zhao; Dan Xu; Shenjie Li; Yueyao Yang; Guohua Zhu; Zhefu Yu; Junpeng Li; Bingcheng Lin; Minghui Zheng; Rong Jin (Journal of Hazardous Materials, 2026)

One stone, two birds: Preparation of nutritionally fortified and easy-to-swallow 3D printed pea protein gel based on high internal phase emulsions - Wei Liang; Junhong Xie; Qiannan Zhao; Chenghong Jiang; Xiaofeng Zhan; Mingrong Chen; Lu Zhang; Chuan Li; Jianhua Rong; Yang Hu (Food Hydrocolloids, 2026)

Twenty-year field evidence reveals crop-specific impacts of conservation tillage on yield in a rice-wheat system - Yalin Yu; Menghan Dong; Yuanchang Xia; Bin Sun; Yanling Li; Ahmad Latif Virk; Haishui Yang; Feng-Min Li; Shiping Liu; Zheng-Rong Kan (Field Crops Research, 2026)

Reduced graphene oxide enhances emerging contaminants removal in anaerobic wastewater treatment: Synergistic role of adsorption and microbial metabolism - Lianxu Wang; Zixin Zhang; Youfei Zhou; Zhen Lei; Yuan Yang; Yu-You Li; Rong Chen (Bioresource Technology, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

Tropical instability waves and their relationships with large-scale oceanic thermal conditions, revealed in ROMS-based hybrid coupled model of the tropical Pacific - Yinnan Li; Yang Yu; Chuan Gao; Hongna Wang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Rhizosphere fungal community and microbial networks shape N2O emissions and crop yield in a rice-rapeseed rotation system under varying nitrogen levels: A case study from Southwest China - Jin-meng Li; Rong Zhao; Tian-yang Ye; Cong-hua Zhu; Jin Chen; Ping Huang; Xue-qing Yang (Agriculture, Ecosystems & Environment, 2026)

Failure Behavior and Energy Evolution of Granite Containing Pre-existing Fissures Characterized by AE and DIC - Run-ze Zhang; Chuan-xin Rong; Bin Wang; Hua-qiao Xu; Yan-zhe Li; Yang Wang (Applied Geophysics, 2026)

Hydrogeophysical Imaging and Joint Interpretation of Rainfall Infiltration on an Embanked Slope in the Mid-Lower Yangtze Hilly Region - Rong-wen Guo; Chen-yang Li; Zhuo Liu; Deng-kang Wang; Ming Yu (Applied Geophysics, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The MADS-box transcription factor AaRLMA serves a crucial function in sustaining the integrity of cell wall, orchestrating secondary metabolites biosynthesis, and modulating pathogenicity in Alternaria alternata - Rong Li; Yiyang Liu; Xiwang Wang; Pengfei Sun; Meiqi Gao; Yanxia Zhang; Yang Bi; Yongcai Li (Postharvest Biology and Technology, 2026)

Unravelling methylmercury formation in high-altitude Tibetan thermokarst lakes - Xia Lu; Xiaosha Liu; Zhixia Yang; Liang Li; Man Yang; Yu-Rong Liu; Baohua Gu; Cuicui Mu (Journal of Hazardous Materials, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

Optical diagnostic study on the combustion and soot formation process of nanobubble diesel - Han Wang; Liang Guo; Wanchen Sun; Yuying Yan; Hao Zhang; Miao Yang; Mengqi Jiang; Degang Li; Rong Xuan; Junfeng Zhang; Kaiqi Yang (Fuel, 2026)

Amine modified porous carbon aerogel templated by the natural structure of wood for CO2 capture and selective separation - Zhouzhou Yang; Xudong Zheng; Zihuai Xu; Sifan Bao; Wei Sun; Shijie Wang; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2026)

Boosting surface basicity of In2O3 aerogel for high-performance H2S sensors via an in-situ annealing strategy of carbon-composited In(OH)3 - Zheng Yang; Qian Rong; Wei Zhang; Qi Xu; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2026)

Sulfur-induced electronic coupling in g-C3N4/Ti3C2Tx-MXene 2D/2D heterojunction enables highly efficient solar-driven disinfection - Rong Ma; Xiaochun Tao; Shuo Li; Chenglong Chen; Qinqin Liu; Shaosheng Rao; Juan Yang (Chemical Engineering Journal, 2026)

Regulating coordination environment of vanadate cathode for ultralong lifespan zinc-ion batteries - Tingting Lv; Rong Li; Linyu Yang; Shuying Wang; Kunjie Zhu; Jiadong Wu; Hui Yao; Haibing Li; Kamal Toqtarhan; Hongyu Mi; Anqiang Pan (Chemical Engineering Journal, 2026)

Crystal-facet regulation of SnO₂ {221} and {110} for selective detection of dimethyl carbonate and H2 gases in battery thermal runaway - Xun Shen; Aijun Yang; Ruochen Ding; Kehan Bo; Jifeng Chu; Pengxu Chen; Chenhui Li; Hongye Yuan; Huan Yuan; Mingzhe Rong; Xiaohua Wang (Chemical Engineering Journal, 2026)

Kinetics of air mixing–anaerobic digestion: High organic substrate concentrations enhance system resistance to oxygen stress - Kailun Song; Huan Chen; Yue Zhao; Li Chen; Rong You; Yilin Wang; Hongnan Yang; Wenguo Wang; Liangwei Deng (Chemical Engineering Journal, 2026)

Phthalocyanine-based prodrug with H₂S-triggered domino cascade for photodynamic and multiple-mechanism synergistic anti-metastatic therapy - Mengyu Yao; Qi-Qi Yang; Huang-Hao Tang; Xue-Yan Li; Wei Xie; Chao Wang; Song Yang; Xingshu Li; Mei-Rong Ke; Jian-Dong Huang (Chemical Engineering Journal, 2026)

Operational thresholds and microbial mechanisms in high-solid anaerobic membrane bioreactors treating swine wastewater: from process performance to metabolic pathways - Yu Li; Gaojun Wang; Yuan Yang; Lingsen Liu; Xiaohong Dang; Yu-You Li; Rong Chen (Bioresource Technology, 2026)

Transforming Camellia oleifera meal into feedstuff: Enhancing value through detoxification and fermentation - Yiyan Cui; Yuheng Lei; Zhenming Li; Zhichang Liu; Min Song; Dun Deng; Zhimei Tian; Ting Rong; Pan Yang; Xianyong Ma; Miao Yu (Bioresource Technology, 2026)

Robust copper/mesoporous silica catalyst for efficient furfural hydrogenation to furfuryl alcohol - Xin-Yu Xiao; Jie Zhang; Rong Wang; Qi Wang; Hai-Song Li; Jing-He Yang (Biomass and Bioenergy, 2026)

Plant-soil feedback driven by root-associated fungal communities accelerates the secondary succession of bare saline-alkaline grassland patches - Xiaona Zheng; Yuhong Yin; Dan Yang; Jingjuan Bi; Wenlong He; Siya Li; Xiao Liang; Jigui Chen; Rong Wang; Zhiying Guo; Xing Li; Tao Zhang; et al. (Plant and Soil, 2026)

Biota occurrence, accumulation, disposition and toxic effect of chlorinated paraffins - Huiming Zhang; Yutong Yang; Mu Zhang; Xue Li; Yan Zhang; Shufen Han; Rong Chen; Jun Yang; Jianyun Zhang (Environmental Geochemistry and Health, 2026)

Organic fertilization improves activities of phosphomonoesters hydrolase in rhizosphere to facilitate phosphorus acquisition in cucumber and accumulates organic phosphorus in soil - Bingshuang Wang; Yuan Wang; Xihe Zhang; Xiaodan Hu; Shujun Li; Yifei Sun; Yang Wang; Yan Sun; Ziwei Dai; Yunsheng Lou; Rong Li; Guohua Xu; et al. (Applied Soil Ecology, 2026)

Fatal infection of a novel canine/human reassortant H3N2 influenza A virus in the zoo-housed golden monkeys - Xia Wen; Rong Chen; Yingjun Lv; Jinzhu Geng; Jingjing Guo; Yaru Sun; Aohan Yang; Yuhao Dong; Meirong Li; Changlin Deng; Guodong Wang; Yongjie Liu (Veterinary Microbiology, 2026)

Contrasting impacts of wheat rhizosphere and hyphosphere on methane and nitrous oxide emissions under straw incorporation - Baowei Huang; Yongcheng Wu; Zheng-Rong Kan; Fede Berckx; Petra Fransson; Qian Zhang; Feng-Min Li; Martin Weih; Haishui Yang (Soil and Tillage Research, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Hydroclimate forcing and anthropogenic impacts trigger an early (∼1650 cal yr BP) regime shift in Chenghai Lake (China) - Qian Wang; John P. Smol; Kathleen M. Rühland; Rong Wang; Xiangdong Yang; Enlou Zhang; Yanjie Zhao; Yanling Li (Quaternary Science Reviews, 2026)

Widespread incongruence in the phylogenomics of the ancient land plant lineage, Selaginellaceae (lycophytes) - Jing Zhao; Hong Yu; Carl J. Rothfels; Jian-Jun Yang; Shao-Li Fang; Zhao-Rong He; Li-Bing Zhang; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2026)

Coordinated horizontal transfer of multiple genes assembles a carotenoid biosynthesis pathway in aphids - Rong Hu; Jun Wu; Siying Li; Peiyu Yang; Gang Wu; Changying Niu; Shuai Zhan; Yazhou Chen (Insect Biochemistry and Molecular Biology, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Revealing the role of spin state in catalysis: Medium spin Fe3+ catalyst for lithium‑sulfur batteries - Xin Dong; Rong Yang; Xifei Li; Peiying Li; Yurou Wang; Xuchen Li; Hongyu Shang; Jiaze Li; Chaojiang Fan; Yinglin Yan; Yunhua Xu (Chemical Engineering Journal, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Ginsenosides secreted by Panax notoginseng promotes the growth and pathogenicity of Fusarium oxysporum through enhancing antioxidant capacity - Lifen Luo; Rong Lu; Rong Yin; Guangxiang Tian; Yiwen Li; Guixiang Li; Hongwei Zhu; Jianqiang Miao; Jianjun Hao; Xili Liu; Shusheng Zhu; Min Yang (Plant and Soil, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Total Saponins of Panax Notoginseng Leaves Modulate the "Microglial-NLRP3/Caspase-1" Axis associated with Gut Microbial/SCFAs Alterations: Correlative Insights into Cognitive Improvement in Senescence - Lan Sun; Jiarong Du; Yuan Xu; Shanshan Wang; Yao Zhang; Rong Yuan; You Lv; Longyan Ding; Yanling Jin; Yu Ren; Xiaoman LV; Jiali Yuan; et al. (Molecular Neurobiology, 2026)

Nitrification-driven nitrogen mineralization in drylands: regulation by human activity intensity and soil microclimate - Rong Yang; Kai Sun; Shiyang Chen; Wenzhi Zhao; Shujun Song; Xiaojun Li (Journal of Soils and Sediments, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)